Impact at two years of an intervention on empowerment among medical care teams: study protocol of a randomised controlled trial in a large French university hospital - Cougot, Baptiste (BMC Health Serv Res, 2019)
BACKGROUND: Empowerment of hospital workers is known as a key factor of organizational performance and occupational health. Nevertheless, empowering workers remains a real challenge. As in many traditional organizations, hospitals follow a bureaucratic model defined by a managerial culture of control and a stratified organization, which at once weaken professionals’ mastery of their work and hinder their commitment and performance. Based on the existing literature this protocol describes a new managerial and organizational transformation program as well as the study design of its effect on worker empowerment in a large French public hospital. The project is funded by the French Ministry of Health for a total of 498,180 €. METHODS: This study is a randomized controlled trial conducted in a French university hospital complex (CHU). The CHU comprises 12 sub-centers (SC) with about 20 care units and 1000 employees each. Randomization is performed at SC level. The intervention lasts 12 months and combines accompaniment of healthcare teams, frontline managers and SC directors to empower first-line professionals in the experimental SC. Quantitative outcome measurements are collected over 2 years during mandatory check-ups in the occupational medicine department. The primary outcomes are structural and psychological empowerment, motivational processes, managerial practices, working conditions, health and performance. Mixed linear modeling is the primary data analysis strategy. DISCUSSION: The protocol was approved by the CHU health ethics committee. The results of the analysis of the intervention effects will be reported in a series of scientific articles. The results will contribute to reflection on prevention and management policies, and to the development of Workplace Quality-of-Life. If the intervention is a success, the system will warrant replication in other SCs and in other health facilities. TRIAL REGISTRATION: The study was retrospectively registered at ClinicalTrials.gov on July 4, 2019 (NCT04010773).